Feasibility study of using digital twins for conceptual design of air-quenching processes - Bi, Zhuming; Mueller, Donald; Mikkola, Aki (International journal of advanced manufacturing technology, 2024)
The concepts of digital twins (DTs) have been widely studied to predict system performance, shorten design cycles, and implement preventive maintenance, but mainly, in large-scale enterprises. It is extremely beneficial to the whole manufacturing sector, since DTs can be readily implemented in small and medium-sized enterprises (SMEs) with basic computer aided engineering (CAE) tools; over 95% enterprises are SMEs. This paper aims to prove the feasibility of using commercial CAE tools, such as SolidWorks Simulation, to design air-quenching processes for SMEs. SMEs can benefit to explore new business opportunities, reduce system design cycle, and improve existing air-quenching processes. To our knowledge, it will be the first work of adopting DTs in conceptual design of an air-quenching process in sense that (1) the need of simulating an air-quenching process before physical implementation is discussed thoroughly; (2) heat transfer processes are classified, governing mathematical models for various heat transfer behaviors are introduced to present an evaluation model of a heat transfer process; (3) main process variables of air-quenching are identified; (4) a DT of an air-quenching process is developed and simulated to verify the capabilities of commercial SolidWorks Simulation; (5) case studies are developed to show how a CAE tool can be used in DTs. The findings from the reported work are summarized with a debrief of our future work.